Tradisi Gawai sebagai Pendorong Kohesi Sosial bagi Masyarakat Suku Dayak Kalimantan Barat - Yusrina Dwi Hariyanti; Onny Fransinata Anggara (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The gawai tradition is an expression of the Dayak tribe's gratitude to Jubata as well as a momentum for Dayak tribes from various regions to meet. The aim of this research is to understand and describe the gawai tradition as a booster of social cohesion for the Dayak people in West Kalimantan which is studied based on the cohesion aspect according to Forsyth which consists of social strength, unity, attraction and cooperation. The research method uses a phenomenological approach and is analyzed using interpretative phenomenological analysis. The research results show that the Gawai tradition can encourage social cohesion through contained values so that the community’s desire emerges to unity amidst diversity.